The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00380-022-02208-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maximum-sized visually guided laser balloon and cryoballoon ablation

Abstract: Balloon ablation therapy has recently been used for atrial fibrillation (AF) ablation. Laser balloons possess the property in which the balloon size can be changed. Standard laser balloon ablation (Standard LBA) was followed by additional ablation using a maximally extended balloon (Extended LBA) and its lesion characteristics were compared to cryoballoon ablation (CBA), another balloon technology. From June 2020 to July 2021, patients with paroxysmal AF who underwent an initial pulmonary vein (PV) isolation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Six studies ( 6 , 7 , 11 14 ) provided information on procedural time of LBA and CBA. Results demonstrated that, LBA had a significantly longer procedural time than CBA (WMD = 38.03 min, 95% CI: 13.48–62.58 min, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies ( 6 , 7 , 11 14 ) provided information on procedural time of LBA and CBA. Results demonstrated that, LBA had a significantly longer procedural time than CBA (WMD = 38.03 min, 95% CI: 13.48–62.58 min, p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…Seven clinical trials (6,7,(10)(11)(12)(13)(14) from 88 potentially relevant studies were finally included in the meta-analysis (Figure 1). A total of 637 patients receiving initial ablation for PAF (LBA, n = 311 vs. CBA, n = 326) were studied.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For instance, left atrial voltage mapping may illustrate the isolated surface area and elucidate the degree of myocardial injury in each procedure. 2 Their finding that PFA was associated with the lowest inflammatory reaction contradicts the aforementioned result. The authors hypothesized that PFA selectively injures myocytes, which have a lower threshold for electroporation, thereby minimizing the inflammatory reaction.…”
mentioning
confidence: 89%